Designing Information Technology Governance in Trading Companies Using COBIT 2019 Framework - Loppies, Marthin Wilheim; Fibriani, Charitas (Journal of Information System and Informatics, 2023)
Mooi Brand Salatiga, a company in the clothing retail sector, has implemented various information systems (IS) to enhance its business processes. These systems include social media platforms such as WhatsApp, Instagram, and Facebook, a Sales Information System for cashiers, and a website. However, Mooi Brand Salatiga often encounters several challenges with the use of these IS, including the lack of system integration, an overreliance on current technology, and an inability to develop independent information systems. COBIT 2019, a systematic and comprehensive framework, offers potential solutions to support companies in efficiently managing and monitoring their information technology. This study leads to the development of an improved pattern for information technology management at Mooi Brand Salatiga, addressing these challenges and paving the way for enhanced operational efficiency and technological autonomy.